The CUC1 and CUC2 genes promote carpel margin meristem formation during Arabidopsis gynoecium development - Kamiuchi, Yuri; Yamamoto, Kayo; Furutani, Masahiko; Tasaka, Masao; Aida, Mitsuhiro (Frontiers in Plant Science, 2014)
Carpel margin meristems (CMMs), a pair of meristematic tissues present along the margins of two fused carpel primordia of Arabidopsis thaliana, are essential for the formation of ovules and the septum, two major internal structures of the gynoecium. Although a number of regulatory factors involved in shoot meristem activity are known to be required for the formation of these gynoecial structures, their direct roles in CMM development have yet to be addressed. Here we show that the CUP-SHAPED COTYLEDON genes CUC1 and CUC2, which are essential for shoot meristem initiation, are also required for formation and stable positioning of the CMMs. Early in CMM formation, CUC1 and CUC2 are also required for expression of the SHOOT MERISTEMLESS gene, a central regulator for stem cell maintenance in the shoot meristem. Moreover, plants carrying miR164-resistant forms of CUC1 and CUC2 resulted in extra CMM activity with altered positioning. Our results thus indicate that the regulatory proteins controlling shoot meristem activity also play critical roles in elaboration of the female reproductive organ through the control of meristematic activity.